Medical Image-Based Hemodynamic Analyses in a Study of the Pulmonary Artery in Children With Pulmonary Hypertension Related to Congenital Heart Disease - Wang, Liping; Liu, Jinlong; Zhong, Yumin; Zhang, Mingjie; Xiong, Jiwen; Shen, Juanya; Tong, Zhirong; Xu, Zhuoming (Frontiers in Pediatrics, 2020)
Objective: Pulmonary hypertension related to congenital heart disease (PH-CHD) is a devastating disease caused by hemodynamic disorders. Previous hemodynamic research in PH-CHD mainly focused on wall shear stress (WSS). However, energy loss (EL) is a vital parameter in evaluation of hemodynamic status. We investigated if EL of the pulmonary artery (PA) is a potential biomechanical marker for comprehensive assessment of PH-CHD. Materials and Methods: Ten PH-CHD patients and 10 age-matched controls were enrolled. Subject-specific 3-D PA models were reconstructed based on computed tomography. Transient flow, WSS, and EL in the PA were calculated using non-invasive computational fluid dynamics. The relationship between body surface area (BSA)-normalized EL (E.) and PA morphology and PA flow were analyzed. Results: Morphologic analysis indicated that the BSA-normalized main PA (MPA) diameter (DMPAnorm), MPA/aorta diameter ratio (DMPA/DAO), and MPA/(left PA + right PA) [DMPA/D(LPA+RPA)] diameter ratio were significantly larger in PH-CHD patients. Hemodynamic results showed that the velocity of the PA branches was higher in PH-CHD patients, in whom PA flow rate usually increased. WSS in the MPA was lower and E. was higher in PH-CHD patients. E. was positively correlated with DMPAnorm, DMPA/DAO, and DMPA/D(LPA+RPA) ratios and the flow rate in the PA. E. was a sensitive index for the diagnosis of PH-CHD. Conclusion:E. is a potential biomechanical marker for PH-CHD assessment. This hemodynamic parameter may lead to new directions for revealing the potential pathophysiologic mechanism of PH-CHD.